2002
DOI: 10.1021/la025882p
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanics and Microcalorimetric Investigations of the Effects of Molecular Water on the Aggregation of Asphaltenes in Solutions

Abstract: The interaction of two model asphaltene molecules from the Athabasca sand oil with a water molecule in a toluene solution was studied by means of molecular mechanics calculations. It was found that water forms bridging H bonds between the heteroatoms of asphaltenes with a considerable span in energies. The stronger H bond found has energies higher than those corresponding to the stacking of the aromatic areas of the same asphaltene molecules. This shows that the water molecule may generate additional mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 12 publications
5
61
0
1
Order By: Relevance
“…This latter view supports other results from simulation and experiment, that low water concentrations promote asphaltene nanoaggregation in toluene solution [13], which is suggested to involve intermolecular H-bonded water bridges and asphaltene heteroatoms, e.g.…”
Section: Introductionsupporting
confidence: 90%
“…This latter view supports other results from simulation and experiment, that low water concentrations promote asphaltene nanoaggregation in toluene solution [13], which is suggested to involve intermolecular H-bonded water bridges and asphaltene heteroatoms, e.g.…”
Section: Introductionsupporting
confidence: 90%
“…The main technique applied is isothermal titration calorimetry (ITC). However, it has never had an extended application to petroleum species (Dietz, Blaha, and Li 1977;Andersen et al 2001;Murgich et al 2002;Merino-Garcia and Andersen 2003). The advantage of this ITC technique above others is that it allows the determination of both the CMC and the enthalpy of surfactant micellization in a single experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The polar heteroatoms of the asphaltene are involved in the formation of the H bonds with water. Murgich et al 40 performed molecular mechanics calculations and titration calorimetry experiments to investigate the H bonds between asphaltene heteroatoms and water. The study showed that water enhances the association of asphaltene monomers to form dimers because of the formation of H bonds with water molecules.…”
Section: Resultsmentioning
confidence: 99%